Incidence and risk factors of delayed postoperative hyponatremia after endoscopic endonasal surgery for Rathke’s cleft cyst: A single-center study - Qian, Ao; Zhou, Jing; Yu, Jiaojiao; Huo, Gang; Wang, Xiaoshu (Frontiers in Surgery, 2022)
Backgroud: Delayed postoperative hyponatremia (DPH) is common for sellar lesions. However, the true prevalence and associated factors of DPH after endoscopic endonasal surgery (EES) for Rathke cleft cyst (RCC) have not been studied in a large patient cohort. Methods: A retrospective analysis was conducted over 6 years at our institution, and patients with RCC treated by EES were enrolled according to our inclusion criteria. Patient demographics, clinical characteristics, images, and surgical procedures were documented. Serum sodium was routinely measured before surgery, on postoperative day one, and every two days thereafter until discharge. For patients with DPH, electrolyte, hematocrit, serum protein levels, and plasma and urinary osmolality were daily measured to explore potential etiology. Results: Of the 160 eligible patients, 35 (21.9%) developed DPH, which was similar to other sellar lesions, except craniopharyngioma, in the same period in our institution. Significant risk factors suggested by univariate analysis were cyst location, requirement of postoperative hydrocortisone therapy, postoperative meningitis, diabetes insipidus, intraoperative cerebrospinal fluid (CSF) leakage and aggressive resection of cyst wall (all p<0.05). In multivariate analysis, suprasellar location (OR 8.387, 95%CI 1.014-69.365, p=0.049), requirement of postoperative hydrocortisone therapy (OR 4.208, 95%CI 1.246-14.209, p=0.021), and intraoperative CSF leakage (OR 6.631, 95%CI 1.728-25.440, p=0.006) were found to be the independent predictors of DPH. Conclusion: DPH is a common complication after EES for RCC. Suprasellar location, requirement of postoperative hydrocortisone therapy, and intraoperative CSF leakage are the most reliable risk factors. Cortisol deficiency and syndrome of inappropriate antidiuretic hormone (SIADH) are considered as the main etiologies of DPH in RCC. Conservative excision of cyst wall may reduce DPH occurrence.